2017
DOI: 10.1007/s00429-017-1381-7
|View full text |Cite
|
Sign up to set email alerts
|

Co-localization of the cannabinoid type 1 receptor with corticotropin-releasing factor-containing afferents in the noradrenergic nucleus locus coeruleus: implications for the cognitive limb of the stress response

Abstract: The noradrenergic system has been shown to play a key role in the regulation of stress responses, arousal, mood, and emotional states. Corticotropin-releasing factor (CRF) is a primary mediator of stress-induced activation of noradrenergic neurons in the nucleus locus coeruleus (LC). The endocannabinoid (eCB) system also plays a key role in modulating stress responses, acting as an "anti-stress" neuro-mediator. In the present study, we investigated the cellular sites for interactions between the cannabinoid re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 118 publications
2
12
0
Order By: Relevance
“…While electrophysiology experiments were carried out in CB1r-KO mice, Western blot and ELISA experiments were carried out in CB1r/CB2r-KO mice due to tissue availability. Many immunohistochemical studies have identified CB1r as an abundant protein in the LC, both directly on the noradrenergic neurons as well as on presynaptic afferents synapsing onto LC-NE dendrites and cell bodies (Scavone et al, 2010; Wyrofsky et al, 2017). While CB2r is traditionally thought to play a role in the periphery and immune responses (Castillo et al, 2012), growing accumulating evidence suggests that it does in fact play a role in neuronal signaling in some select brain regions (Van Sickle et al, 2005; Gong et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While electrophysiology experiments were carried out in CB1r-KO mice, Western blot and ELISA experiments were carried out in CB1r/CB2r-KO mice due to tissue availability. Many immunohistochemical studies have identified CB1r as an abundant protein in the LC, both directly on the noradrenergic neurons as well as on presynaptic afferents synapsing onto LC-NE dendrites and cell bodies (Scavone et al, 2010; Wyrofsky et al, 2017). While CB2r is traditionally thought to play a role in the periphery and immune responses (Castillo et al, 2012), growing accumulating evidence suggests that it does in fact play a role in neuronal signaling in some select brain regions (Van Sickle et al, 2005; Gong et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most widely used recreational drugs in the world, cannabis, often causes feelings of relaxation and euphoria (Velez et al, 1989; Green et al, 2003; Di Marzo et al, 2004); however, chronic usage can be anxiogenic and produce dysphoria (Reilly et al, 1998). Via activation of cannabinoid type 1 receptors (CB1r), cannabinoids are known to affect attention and anxiety (Witkin et al, 2005; Pattij et al, 2008; Hill and Gorzalka, 2009), in part via actions on noradrenergic circuitry (Carvalho et al, 2010; Carvalho and Van Bockstaele, 2012; Wyrofsky et al, 2017). There are, however, some discrepancies within the cannabinoid field.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, recent immunofluorescence studies from our laboratory have demonstrated that CB1r are co-localized with CRF in the rat LC (Fig. 3A) (Wyrofsky et al, 2017). Additionally, using Phaseolus Vulgaris Leucoagglutinin (PHAL) as an anterograde tracer injected into the amygdala, CB1r are directly positioned to regulate CRF release from amygdalar limbic afferents (Fig.…”
Section: Ecb Regulation Of Stress Circuitrymentioning
confidence: 89%